African human rights system : origin and evolution origin and evolution - Oteng Kufuor, Kofi. (New York : Palgrave Macmillan, 2010)
"This book challenges the received scholarship on the origins of the African Charter on Human and Peoples' Rights. The author applies economic and social theory to understanding the African Commission's dynamic treaty interpretation, and the Commission's strategic manipulation of the Rules of Procedure to strengthen the African human rights system"--Provided by publisher.
The origin of the African human rights system -- The African Commission and the rewriting of the African Charter -- The African Commission and its treatment of economic, social, and cultural rights -- System evolution through the African Commission's rules of procedure -- The fragmentation of the African human rights system -- The future direction of the African human rights system.
Includes bibliographical references and index.
Keywords: African Commission on Human and Peoples' Rights; African Commission on Human and Peoples' Rights; Human Rights Africa (Organization); African Charter on Human and People's Rights -- (1981); African Charter on Human and People's Rights (1981); Human rights -- Africa